2012
DOI: 10.1186/1735-2746-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of reverse osmosis technology for selected antibiotics removal from synthetic pharmaceutical wastewater

Abstract: This study addresses the possibility for low pressure reverse osmosis membrane (RE 2521, CSM) process to serve as an alternative to remove selected antibiotics (ampicillin and amoxicillin) from synthetic wastewater by changing operating conditions such as pH = 3, 6.5 and 10; Pressure = 9, 11 and13 (bar); antibiotic concentration = 10, 255 and 500(mg/L), and temperature = 20, 30 and 40°C. The experiment was designed based on Box-benken, which is a Response Surface methodology design (RSM), using Design Expert s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…In order to remove emerging contaminants from water, advanced processes such as UV/H 2 O 2 oxidation [8], photo-Fenton [9], nano and ultra-filtration [10], reverse osmosis [11] and adsorption onto activated carbon [12] have been successfully used. Nevertheless, the application of these processes may be quite expensive and, furthermore, some of them may give place to undesired by-products [13].…”
Section: Introductionmentioning
confidence: 99%
“…In order to remove emerging contaminants from water, advanced processes such as UV/H 2 O 2 oxidation [8], photo-Fenton [9], nano and ultra-filtration [10], reverse osmosis [11] and adsorption onto activated carbon [12] have been successfully used. Nevertheless, the application of these processes may be quite expensive and, furthermore, some of them may give place to undesired by-products [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study results agree with those of Gholami et al, and Sahar et al who reported the significant rejection of pollutants from waste effluents. 21,22 Figure 8 shows the results of NF for wastewater treatment containing cations and anions using the old NF and new NF membranes. The old membrane worked for 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the application of the RO membrane was recommended for the removal of selected antibiotics up to 95 % from synthetic waste effluent. 21 In addition pressure-driven membrane processes, particularly nanofiltration (NF) and reverse osmosis (RO) have also been gaining attention in the past decade and their application in drinking-water treatment has been the focus of many researchers. 22 …”
Section: Municipal Wastewatermentioning
confidence: 99%
“…The 20 resistant bacteria may cause disease that cannot be treated by 21 conventional antibiotics; therefore, AMX wastes need to be treated 22 before disposal to the environment [3]. 23 There are many methods for AMX removal from sewage water, 24 such as nanofiltration membrane, electrocoagulation, electrochem- 25 ical oxidation, biodegradation, reverse osmosis, ozonation, fenton 26 oxidation, catalytic degradation, and adsorption [4][5][6][7][8][9][10][11][12]. Adsorption 27 has been proven to be an effective process for removal of various 28 antibiotic pollutants from aqueous solutions because of its simple 29 design, flexibility, easy operation, suitability for batch and continu- 30 ous processes, possibility of regeneration and reuse, low capital cost, 31 and capability to remove wide range of pollutant concentrations [13].…”
Section: Introductionmentioning
confidence: 99%